2013
DOI: 10.3389/fpsyg.2013.00862
|View full text |Cite
|
Sign up to set email alerts
|

Lexical neighborhood effects in pseudoword spelling

Abstract: The general aim of this study is to contribute to a better understanding of the cognitive processes that underpin skilled adult spelling. More specifically, it investigates the influence of lexical neighbors on pseudo-word spelling with the goal of providing a more detailed account of the interaction between lexical and sublexical sources of knowledge in spelling. In prior research examining this topic, adult participants typically heard lists composed of both words and pseudo-words and had to make a lexical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 55 publications
1
24
0
1
Order By: Relevance
“…Additionally, we found that more target spellings were produced for nonwords having low enemies than those having high enemies across prime and control conditions. While previous work has found an influence of word neighbors on nonword spelling, only the influence of "friends" was examined [19]. We extended these findings to the influence of word enemies and the influence of the frequency of word neighbors…”
Section: Word Neighbor Influencesmentioning
confidence: 88%
See 4 more Smart Citations
“…Additionally, we found that more target spellings were produced for nonwords having low enemies than those having high enemies across prime and control conditions. While previous work has found an influence of word neighbors on nonword spelling, only the influence of "friends" was examined [19]. We extended these findings to the influence of word enemies and the influence of the frequency of word neighbors…”
Section: Word Neighbor Influencesmentioning
confidence: 88%
“…The work of Tainturier et al [19] suggests that a lexical influence on the operation of the sublexical system may be a result of the activation of the spellings of word neighbors upon the aural presentation of a nonword. Those spellings are more likely to be selected to spell the nonword.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations